PENGOLAHAN DAN PENGKEMASAN KULINER LOKAL DI DESA WISATA TISTA KECAMATAN KERAMBITAN KABUPATEN TABANAN - A.M. Putra; I.N.J. Ariana; A.S. Sulistyawati; I.N.T. Sutaguna; N. Narottama (Buletin Udayana Mengabdi, 2022)
This activity aims to empower the community in developing local products made from local ingredients. Community agricultural products are processed and packaged into economically valuable products, it is hoped that agricultural activities can be maintained and reduce the conversion of agricultural land. The method used is through observation and empowerment programs with a model approach including: Community Participation Model, Community Entrepreneurship Capacity Building Model, and Technology Transfer Model. The result of this activity is the creation of culinary products originating from local ingredients by increasing community participation to support the development of the Tista Rural Tourism, so that it will become an added value to the community with the growth of home industries. Activities include: introduction of tools/materials, hands-on practice, and product packaging. Community participation is very high in this activity. Keywords: Culinary, Packaging, Products, Entrepreneurship, Tourism.